Biosorption of CU(II) Ions by Leucaena Leucocephala Leave from Aqueous Solution - M A, Azmi; Nadiah, Mokhtar; N F, Shoparwe; H, Shukor (IOP Science, 2021)
As a preliminary study, this project aims to remove the copper (Cu II) from aqueous solutions using Leucaena leucocephala leaves. Effect of free cell and immobilized form of biosorbent on adsorption capacity were evaluated in this study. Kinetic models of pseudo-first order, second order and equilibrium isotherms of Langmuir and Freundlich were used to predict the efficiency of Cu2+ absorption by Leucaena leucocephala leaves adsorption system. The functional groups involved during the adsorption were identified using Fourier Transform Infrared (FTIR) whereby the Leucaena leucocephala leaves has the large amount of hydroxyl functional groups at the wavelength of 3411.66 cm-1. Atomic Absorption Spectroscopy (AAS) were used to measure the metal concentration before and after the adsorption process. The maximum percentage removal of the Cu2+ was achieved by immobilized form of Leucaena leucocephala leaves as biosorbent in aqueous solutions with a 72.3% of removal. Adsorption kinetics of pseudo-second order was well fitted with the adsorption data with the R2 of 0.9622. In addition, the results reveal that Langmuir isotherm was the best model to explain the adsorption of Cu2+ using immobilized Leucaena leucocephala leaves with the R2 of 0.9974. This result showed that Leucaena leucocephala leaves as an effective and potential biosorbent for the adsorption of Cu2+ from the wastewater